Comparison of outcomes for supine vs. prone position ERCP: a systematic review and meta-analysis - Mashiana, Harmeet Singh; Jayaraj, Mahendran; Mohan, Babu Pappu; Ohning, Gordon; Adler, Douglas G. (Endoscopy International Open, 2018)
Background While endoscopic retrograde cholangiopancreatography (ERCP) is usually performed in the prone position, some studies have advocated for ERCP in the supine position. Studies comparing the technical success and safety outcomes have shown variable results. We performed a systematic review and meta-analysis of studies reporting the comparison between the two positions for ERCP outcomes.Methods We conducted a search of electronic databases and conference proceedings including PubMed, EMBASE, and Web of Science databases (from inception through October 2016) to identify studies that reported the comparison of technical success and safety outcomes between supine and prone ERCP. The primary outcome was to estimate the pooled rates of technical success. The secondary outcome was to estimate the risks of complications, such as cardiopulmonary and post-ERCP pancreatitis (PEP).Results Six studies reporting on 309 supine and 1415 prone ERCPs were identified. The pooled technical success rates for completion of ERCP in supine and prone positions were 89.1 % (95 %CI = 80.9 – 94.0) and 95.6 % (95 %CI = 91.5 – 97.7), respectively. The pooled rates for complications (cardiopulmonary and PEP) in the supine position were 37.5 % (95 %CI = 19.1 – 60.3) and 3.5 % (95 %CI = 1.6 – 7.3), respectively. The pooled rates for complications (cardiopulmonary and PEP) in the prone position were 41.0 % (95 %CI = 20.9 – 64.8) and 3.9 % (95 %CI = 2.4 – 6.4), respectively. The mean time required for the procedure was 30 minutes and 29.8 minutes for supine and prone positions, respectively. Substantial heterogeneity was noted in the analysis.Conclusion Prone ERCPs have a higher technical success rate with a slightly lower mean duration but a higher number of adverse events. The decision with regard to patient position should be made after evaluating the overall clinical scenario.